2020
DOI: 10.34117/bjdv6n3-281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total phenolic content and antioxidant activity of different extracts of Agaricus blazei Murril

Abstract: Comparison of total phenolic content and antioxidant activity of different extracts of Agaricus blazei Murril Comparação do conteúdo fenólico total e atividade antioxidante de diferentes extratos de Agaricus blazei Murril

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In addition to these, variables such as sample size, solvent flow and ecstatic extraction time also influence the extracts yield, as they interfere with the mass transfer rate. Soares et al (2020) reported in their study that aqueous and hydroalcoholic extraction, at 50 and 70%, showed a higher content of phenolic compounds when compared to extraction using absolute ethanol.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to these, variables such as sample size, solvent flow and ecstatic extraction time also influence the extracts yield, as they interfere with the mass transfer rate. Soares et al (2020) reported in their study that aqueous and hydroalcoholic extraction, at 50 and 70%, showed a higher content of phenolic compounds when compared to extraction using absolute ethanol.…”
Section: Resultsmentioning
confidence: 96%
“…Oxidative stress arises when there is a disparity between the generation of ROS and the capacity of the antioxidant defense system [13]. However, when present in larger quantities, ROS cause damage to macromolecules including lipids, carbohydrates, nucleic acids, and proteins, which may induce cell aging, and lead to oxidative stress [14][15]. These radicals react with oxygen to form primary oxidation products, primarily hydroperoxides.…”
Section: Role Of Bioactive Compounds In Food Preservationmentioning
confidence: 99%
“…The concentrations of phenolic compounds in the crude extract (grease) that was obtained by the dynamic maceration process with solvent depletion and the spray-dried crude extract were determined using the Folin-Ciocalteu method described by Soares et al (2020) with some modifications. An aliquot of the sample (extract and water-white) will be diluted to a final volume of 1 ml of distilled water.…”
Section: Determination Of Total Phenolic Compoundsmentioning
confidence: 99%